Kalmusia variispora (Didymosphaeriaceae, Dothideomycetes) Associated with the Grapevine Trunk Disease Complex in Cyprus - Makris, Georgios; Sandoval-Denis, Marcelo; Crous, Pedro W; Kanetis, Loukas (My University, 2025)
Grapevine trunk diseases (GTDs) are widespread worldwide, causing serious economic losses to the vitiviniculture industry. The etiology of the complex pathogenic mycobiome associated with this group of diseases is critical to implementing appropriate management strategies. Diseased grapevines exhibiting typical GTD symptoms were collected from vineyards in different provinces of Cyprus, resulting in 19 pycnidial isolates. A subsequent multilocus sequence analysis of six genetic loci (ITS, LSU, SSU, b-tub, tef1-a, and rpb2) identified them as Kalmusia variispora, and twelve representative isolates are included in the phylogenetic analyses. According to pathogenicity trials on two-year-old potted vines (cv. Mavro), all tested isolates were pathogenic, exhibiting light to dark brown discoloration and lesions of varying levels, ranging from 4 to 12.3 cm long. The capacity of K. variispora isolates to produce cell-wall-degrading exoenzymes was qualitatively estimated on solid media. Cellulase, pectinase, and laccase production were evident for all the tested isolates, except isolate CBS 151329, where the latter enzyme was undetected. The severity of the symptoms was consistent with the laccase-producing capacity. The present study confirmed the association of K. variispora with grapevines as a pathogen and represents the first description of this ascomycete as a GTD causal agent in Cyprus. This highly virulent species may play a significant role in the GTD complex, and its biological cycle and epidemiology should be further investigated.
Keywords: grapevine trunk diseases; Cyprus; Didymosphaeriaceae; Kalmusia variispora; Vitis vinifera